Morphological and Electrochemical Characterization of Nanostructured Li4Ti5O12 Electrodes Using Multiple Imaging Mode Synchrotron X-ray Computed Tomography. Issue 12 (1st January 2017) - Kashkooli, Ali Ghorbani; Foreman, Evan; Farhad, Siamak; Lee, Dong Un; Feng, Kun; Lui, Gregory; De Andrade, Vincent; Chen, Zhongwei
Abstract : In this study, synchrotron X-ray computed tomography has been utilized using two different imaging modes, absorption and Zernike phase contrast, to reconstruct the real three-dimensional (3D) morphology of nanostructured Li4 Ti5 O12 (LTO) electrodes. The morphology of the high atomic number active material has been obtained using the absorption contrast mode, whereas the percolated solid network composed of active material and carbon-doped polymer binder domain (CBD) has been obtained using the Zernike phase contrast mode. The 3D absorption contrast image revealed that some LTO nano-particles tend to agglomerate and form secondary micro-sized particles with varying degrees of sphericity. The tortuosity of electrode's pore and solid phases were found to have directional dependence, different from Bruggeman's tortuosity commonly used in macro-homogeneous models. The electrode's heterogeneous structure was investigated by developing a numerical model to simulate galvanostatic discharge process using the Zernike phase contrast mode. The inclusion of CBD in the Zernike phase contrast results in an integrated percolated network of active material and CBD that is highly suited for continuum modeling. The simulation results highlight the importance of using the real 3D geometry since the spatial distribution of physical and electrochemical properties have a strong non-uniformity due to microstructural heterogeneities.